Text-to-Video Generation: Animate-X - Vidyullatha, Akula; Kaushik, Bhoomi; Junaid, Shaik Mohammad; Khan, Zaid (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
This paper introduces a script designed to automate the conversion of textual content into visually engaging videos with synchronized audio narration. The script accepts a plain text file as input and generates a video where each word is animated, allowing for dynamic presentation of textual information. Key features include customizable text attributes such as font size, color, and animation speed, along with dynamic background color transitions for enhanced visual appeal. Utilizing libraries such as `argparse`, `numpy`, `Pillow`, `gtts`, `moviepy`, and `pydub`, the script efficiently processes the input text, computes word durations, and generates corresponding video frames. It seamlessly integrates synthesized audio narration generated from the input text, ensuring coherence between visual and auditory elements in the resulting video. Empirical evaluation and case studies demonstrate the effectiveness and versatility of the script across domains such as e-learning, content marketing, and entertainment. It offers a streamlined approach to converting textual content into multimedia formats, with potential applications in educational tutorials, promotional material, and social media content creation. This paper provides a comprehensive overview of the script's implementation, customization options, and usage instructions. Additionally, it discusses potential applications and compares the script with existing methods in the field of automated video generation from textual input. Overall, the script serves as a valuable tool for content creators seeking to enhance the presentation and accessibility of textual information through dynamic multimedia content generation.